Автоматизація процесів нафтопереробки на підприємстві - Пономаренко, Д. А. (ХНУРЕ, 2025)
Automation of processes at oil refineries is a key factor in improving the efficiency, safety and environmental friendliness of production. This paper is devoted to the development and analysis of automation systems used in the oil refining industry, with a focus on modern technologies and their implementation.
Keywords: нафтопереробка; автоматизація процесів нафтопереробки